2020
DOI: 10.7716/aem.v9i2.1393
|View full text |Cite
|
Sign up to set email alerts
|

Compact Multiband Microstrip Printed Slot Antenna Design for Wireless Communication Applications

Abstract: In this paper, a compact multiband printed antenna is proposed to cover four resonant bands in the range of 1-6 GHz. The antenna structure is inspired from that of the classical multi-cavity magnetron resonator. The antenna comprises a slot annular ring structure in the ground plane of an Isola FR4 substrate having Ԑr = 3.5 and thickness h=1.5 mm. The outer circle of the annular ring is loaded with radial arranged small circular slots. On the opposite side of the substrate, the antenna is fed with a 50-Ohm mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The sizes of the antenna are 116 ×40 ×1.6 mm3. Monopole MPA antenna is proposed for multiband applications [24]. The size of the antenna is 53.8 × 53.8 mm2, and the structure is inspired by multi-cavity magnetron resonator.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The sizes of the antenna are 116 ×40 ×1.6 mm3. Monopole MPA antenna is proposed for multiband applications [24]. The size of the antenna is 53.8 × 53.8 mm2, and the structure is inspired by multi-cavity magnetron resonator.…”
Section: Literature Reviewmentioning
confidence: 99%
“…for achieving multi band operation. A common method for achieving a multiband is to cut slots and slits of different shapes on the patch [20][21][22][23][24][25][26][27][28], the main challenges as reported by other researcher are to determine the proper position of the shorting posts, stubs, slots etc. and measurements of the width and length of the slots, which leads to an overall complicated process to design the antenna.In the proposed work, we have designed and developed a multi band MSA for wireless communication system to operate at 1.8 GHz and 2.4 GHz by cutting a slit with an inclination angle over the MSA rather than other classical approach.…”
Section: Introductionmentioning
confidence: 99%
“…The multi band operation was achieved by using a slot annular ring structure in the ground plane. It helps the antenna to resonate at 1.53-2.11 GHz, 2.9-3.34 GHz, 4.2-4.75 GHz and 4.94-5.39 GHz[24]. F. I. Khalifa, et al reported a U-shaped slot MSA effectively operated at 2.4GHz and 4.6GHz for WLAN applications.…”
mentioning
confidence: 99%
“…In wireless communication systems, many applications operate at frequencies below 6 GHz to ensure high speed guided transmission [1]. For this reason, choosing the low frequencies antenna has declined in recent times [1].…”
Section: Introductionmentioning
confidence: 99%
“…In wireless communication systems, many applications operate at frequencies below 6 GHz to ensure high speed guided transmission [1]. For this reason, choosing the low frequencies antenna has declined in recent times [1]. The antenna is one of the most essential components of wireless communications systems because it is used in both transmitter and receiver sides [2].…”
Section: Introductionmentioning
confidence: 99%